Weight Self-Regulation Process in Adolescence: The Relationship between Control Weight Attitudes, Behaviors, and Body Weight Status - Pich, Jordi; Bibiloni, Maria del Mar; Pons, Antoni; Tur, Josep A. (Frontiers in Nutrition, 2015)
Adolescents’ self-control weight behaviors were assessed (n= 1961; 12-17 years old; 2007-2008) in the Balearic Islands, Spain. The study analyzed the relationships between body weight status, body image and self-weight concern, and actual attempts to lose weight by restrained eating and/or increased exercising. In terms of regulatory focus theory (RFT), we considered that efforts to lose or to maintain weight (successful or failed) would be motivated either by a “promotion focus” (to show an attractive body), a “prevention focus” (to avoid social rejection of fatness), or both. Results showed that 41% of overweight boys and 25% of obese boys stated that they had never made any attempt to lose weight, and 13% and 4% in females. Around half of overweight boys and around a quarter of obese boys stated that they were “Not at all” concerned about weight gain, and girls’ percentages decreased to 13% and 11% respectively. By contrast 57% of normal weight girls monitored their weight and stated that they had tried to slim at least once. Weight self-regulation in females attempted to combine diet and exercise, while boys relied almost exclusively on exercise. Apparent lack of consciousness of body weight status among overweight boys, and more important, subsequent absence of behaviors to reduce their weight clearly challenges efforts to prevent obesity. We argue that several causes may be involved in this outcome, including unconscious emotional (self-defense) and cognitive (dissonance) mechanisms driven by perceived social stigmatization of obesity. The active participation of social values of male and female body image (strong vs. pretty) and the existence of social habituation to overweight are suggested. A better knowledge of psychosocial mechanisms underlying adolescent weight self-control may improve obesity epidemics.